Are you a successful negotiator? A study on the roles of emotional intelligence and cognitive ability in negotiation - Ang, Tian Tian (2011)
The purpose of this study is to determine the effect of emotional intelligence on value creation during the negotiation process. A group of business undergraduates were put through a negotiation simulation exercise. The results concluded that there is a positive relationship between emotional intelligence and value creation. Furthermore, the results also showed that cognitive ability moderates this relationship. These results indicate a need for negotiators to consider the impact of intelligences on value creation and the effect from the interaction between these intelligences in negotiation.